Dual band angle insensitive metamaterial absorber with MgxCa(0.90−x)Ni0.10Fe2O4 based novel microwave flexible substrate for electromagnetic energy harvesting application - Md Shakibul Hasan; Mohammad Tariqul Islam; Abdulmajeed M. Alenezi; Md Moniruzzaman; Ahmed S. Alshammari; Mohamed S. Soliman; Saeed Alamri; Md Samsuzzaman (APL Materials)
This article presents a metamaterial absorber originated on a flexible substrate of MgxCa(0.90−x)Ni0.10Fe2O4. The MgxCa(0.90−x)Ni0.10Fe2O4 substrate is developed using the sol-gel technique, where X25, X50, and X75 represent 25%, 50%, and 75% of the corresponding material concentration, respectively. The dielectric constant values for X25, X50, and X75 are 2.52, 3.05, and 3.44, with loss tangents of 0.0026, 0.004 25, and 0.0062, respectively. The substrate nanoparticles’ morphology is analyzed using x-ray diffraction, energy dispersive x-ray characterization, and field emission scanning electron microscopy. A metamaterial absorber is then designed on this substrate with a dimension of 16 × 16 mm2. The resonator is comprised of three rings with a square-shaped split outer ring, a square-shaped middle ring, and an innermost arrow-shaped structure. It exhibits absorptance peaks of 99.45% and 99.61% at 4.51 and 7.26 GHz, respectively. Metamaterial and absorber properties are investigated with surface current, electric, and magnetic field analysis. The proposed flexible metamaterial absorber (FMMA) exhibits single negative properties, and it also demonstrates an insensitive response up to 75° for both polarization angle and incident angle variation in transverse electric mode. Furthermore, the FMMA demonstrates exceptionally high energy harvesting (EH) efficiencies of 95.11% and 96.02% at 4.51 and 7.26 GHz, respectively. The efficiency is also investigated for various bending conditions. The small size, lightweight, and flexibility of the structure indicate that MgxCa(0.90−x)Ni0.10Fe2O4 based FMMAs have significant potential for EH applications in the C band.